2023
DOI: 10.1037/cpp0000434
|View full text |Cite
|
Sign up to set email alerts
|

Early Weight Loss in Adolescent Weight Management: The Role of the Home Environment

Abstract: Objective: Successful weight loss early in treatment is a key factor for long-term weight management success in adolescence. Yet prior research has not examined factors in the home environment related to risk for increased weight status as potential predictors of early weight management success. The primary goal of the present study was to explore the impact of modifiable household factors on baseline weight status and early weight status change among adolescents participating in an outpatient weight managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Although some studies report direct effects of household chaos on child weight status [ 26 ], others report indirect effects [ 27 ] or no effects [ 28 , 29 ]. One study among adolescents entering a weight management program found higher chaos in the home environment to be associated with higher baseline body mass index and lower short term success in weight loss [ 30 ]. Moreover, sex differences in the association between chaotic home environments and child weight status have been reported in one study of toddlers where an association was found only among boys but not among girls [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies report direct effects of household chaos on child weight status [ 26 ], others report indirect effects [ 27 ] or no effects [ 28 , 29 ]. One study among adolescents entering a weight management program found higher chaos in the home environment to be associated with higher baseline body mass index and lower short term success in weight loss [ 30 ]. Moreover, sex differences in the association between chaotic home environments and child weight status have been reported in one study of toddlers where an association was found only among boys but not among girls [ 25 ].…”
Section: Introductionmentioning
confidence: 99%